Forage Resources in Livestock-Cropping Smallholder Systems. A Case Study of Farmers at Transmigration Areas of Dompu, West Nusa Tenggara - Y A Sutaryono (Faculty of Animal Science, Bogor Agricultural University, 2008)
A study aimed to identify the farmer practice in providing feed for their Bali cattle was undertaken at Satuan Pemukiman A (SPA) sub-village, Manggalewa sub district, Dompu, West Nusa Tenggara, a region of highly variable rainfall patterns and lengthy dry seasons. A critical aspect of this study was the detailed characterization of the availability, quality and usage patterns for existing forage resource within the SPA mixed crop-livestock farming system. The study found that SPA farmers used varying mixtures of free or tethered grazing and cut and carry to supply the forage needs of their cattle. The available grazing was of good quality and supply in the wet season but declined rapidly by early dry season. From mid-dry season on, the vast majority of farmers relied increasingly on cut and carry forage from a range of sources including volunteer pastures, crop residues, shrub legumes and finally other sources such as banana and papaya stem, cashew apple and native tree leaves in the late dry season. Despite some use of high quality shrub legumes such as Leucaena leucocephala and Gliricidia sepium the quantity and quality of available forage was often below maintenance, especially for lactating cows. The study also revealed that existing forage sources such as the shrub legumes L. leucocephala and G. sepium maintained high levels of crude protein and digestibility year round. Greater use of shrub legumes (especially G. sepium) and conserved forages have the potential to significantly reduce the feed gap in the second half of the dry season at SPA. Key words: Bali cattle, smallholder, cut and carry, pasture, shrub legume